MAFLD and glomerular hyperfiltration in subjects with prediabetes, visceral obesity and “preserved” kidney function: A cross-sectional study - Parvanova, Aneliya; Abbate, Manuela; Yañez, Aina Maria; Bennasar-Veny, Miquel; López-González, Ángel Arturo; Ramírez-Manent, José Ignacio; Iliev, Ilian Petrov; Fresneda, Sergio; Arias-Fernandez, Maria; Remuzzi, Giuseppe; Ruggenenti, Piero (Diabetes research and clinical practice, 2023)
•Prediabetes subjects with visceral obesity and eGFR ≥ 60 ml/min are at increased risk of MAFLD.•In these subjects MAFLD is associated with glomerular hyperfiltration.•Presence of MAFLD could potentiate the age-related eGFR decline.•The liver health assessment should be included in the conventional screening approach. To investigate the prevalence of metabolic dysfunction-associated fatty liver disease (MAFLD) in prediabetes, visceral obesity, and preserved kidney function, and explore whether MAFLD is associated with hyperfiltration. We analyzed data from 6697 Spanish civil servants, aged 18–65 years, with fasting plasma glucose ≥ 100 and ≤ 125 mg/dL (prediabetes, ADA), waist circumference ≥ 94 cm in men and ≥ 80 cm in women (visceral obesity, IDF) and de-indexed estimated glomerular filtration rate (eGFR) ≥ 60 ml/min, collected during occupational health visits. The association between MAFLD and hyperfiltration (eGFR > age- and sex-specific 95th percentile) was tested by multivariable logistic regression analyses. Overall, 4213 patients (62.9%) had MAFLD, and 330 (4.9%) were hyperfiltering. MAFLD was more frequent in hyperfiltering than in non-hyperfiltering subjects (86.4% vs 61.7%, P < 0.001). BMI, waist circumference, systolic, diastolic, mean arterial pressure, and prevalence of hypertension were higher in hyperfiltering than in non-hyperfiltering subjects (P < 0.05). MAFLD was independently associated with hyperfiltration, even after adjusting for common confounders [OR (95% CI): 3.36 (2.33–4.84), P < 0.001]. In stratified analyses MAFLD potentiated age-related eGFR decline vs. non-MAFLD (P < 0.001). More than half of subjects with prediabetes, visceral obesity and eGFR ≥ 60 ml/min presented MAFLD that was associated with hyperfiltration and potentiated the age-related eGFR decline.